Gas Pickering Emulsion Templated Hollow Carbon for High Rate Performance Lithium Sulfur Batteries. (14th September 2016) - Li, Matthew; Zhang, Yining; Wang, Xiaolei; Ahn, Wook; Jiang, Gaopeng; Feng, Kun; Lui, Gregory; Chen, Zhongwei
Abstract : A CO2 in water nanoparticle stabilized Pickering emulsion is used to template micrometer sized hollow porous nitrogen doped carbon particles for high rate performance lithium sulfur battery. For the first time, nanoparticles serve the dual role of an emulsion stabilizer and a pore template for the shell, directly utilizing in situ generated CO2 bubbles as template for the core. The minimalistic nature of this method does not require expensive surfactants or additional core templates. Upon polymerization of melamine formaldehyde onto CO2, a robust polymer/silica composite shell is formed and transformed into a porous shell upon washing. The micrometer‐sized hollow morphology in combination with its nitrogen rich porous shell demonstrates impressive rate capabilities of 670 and 500 mAh g −1 even at a high rate of 7C and 9C, respectively. This material also possesses excellent cycle durability, exhibiting a low capacity decay of 0.088%/cycle over 300 cycles. Measurement of the shuttle current and impedance provides interesting insight into the polysulfide mass transfer mechanism of hollow structured sulfur hosts. Abstract : A gas Pickering emulsion is used to synthesize porous hollow carbon, taking advantage of the dual role of the nanoparticle as both an emulsion stabilizer and a pore template for the shell. Impressive rate performance is observed and investigated, providing valuable insight into the mechanistic benefits of hollow structures for lithium sulfur battery applications.